Pendidikan Karakter Melalui Peran Pesantren pada Era Globalisasi di Pondok Pesantren Attholibiyah Bumijawa Tegal - Neli Maulidiyah (La-Tahzan: Jurnal Pendidikan Islam, 2023)
This research is entitled Character Education through the Role of Islamic Boarding School in the Era of Globalization (Case Study of Pondok Pesantren Attholibiyah Bumijawa Tegal). The purpose of this study was to determine the role of Attholibiyah Islamic boarding school in shaping students in the era of globalization, as well as to determine the character of Attholibiyah Islamic boarding school students. The method in this research uses qualitative research methods, this research is included in field research and uses qualitative descriptive analysis. The data sources in this study are primary data sources and secondary data sources, the primary data sources are the caretaker of Attholibiyah Islamic boarding school, Utad/ustadzah, PERSABI administrators, students. Secondary data sources in this study are pesantren archives and related literature. Data collection techniques in this study used techniques, observation, documentation and interviews. The results or conclusions of the research show that the character of Attholibiyah Islamic boarding school students is reflected in everyday life where character values instilled in Attholibiyah Islamic boarding school students such as courtesy, caring, responsibility, patience, independence, and humility. The Attholibiyah Bumijawa Islamic boarding school has carried out the role of pesantren education in shaping the character of students in the era of globalization through the study of the yellow book and the study of reading and writing the Qur'an, providing exemplary examples in daily life in the pesantren, habituation of goodness in daily life in the pesantren, giving advice and punishment and also through extracurricular activities.